La técnica de la mimesis para el desarrollo social en niños y niñas de Educación Inicial - De la Cruz Arteaga, Angie Abigail (2022)
The current work was based on the research line from Cotopaxi Technical University, education and communication for human and social development and the Society and Education research subline, it arose from the existing problems in the "United Nations" Educational Unit located in the Cotopaxi province Saquisilí canton, La Matriz neighborhood; since in the cases educators vast majority do not have constant training on pedagogical strategies, which they can innovate from mimesis as a theatrical representation, getting as a result several difficulties into children emotional part, giving as an effect the empathy and socialization lack inside and outside the classroom, therefore, the playful activities absence harms the infant's learning. For this reason, according to the research, it is proposed the proposal "Smiles Factory: I play, I have fun and I learn by imitating"; which had the aim to develop playful workshops related to mimesis for social development into children with an 4 to 5 years age condition, such a way, that the workshops were elaborated with the constructivist approach, which is very relevant, so that the children develop an environment based on values, such as responsibility, respect and cooperation, adapting their learning through experimentation, artistic and corporal expression, helping in the infant social development. Therefore, by means dynamic and interactive development, through the proposal, it was sought to set a learning link between initial education children, teachers and parents, for an improvement in the infant development and social environment, as well as their abilities and skills. Within these, they have nine workshops, which five are intended to work with infants, two workshops for parents and two to work with teachers from the United Nations Educational Unit. This way, it is concluded, what is important the knowledge about mimesis, since it is a technique, which manages to reach the proposed aim, through the game, achieving collaborative learning together with social development.